(untitled) (TERRA LATINOAMERICANA, 2020)
In the immediate future and the medium term, activities of Scientific and Technological Research, Human Resource Training, and Linkage and Social Appropriation of Knowledge will suffer the hardships of the new restrictions imposed by the new reality of the COVID-19 Pandemic. Societies, economies, Research and Higher Education Institutions that manage to adapt faster to these new challenges and have the structural capacities to make their processes flexible, will have a better chance to fastly overcome this global contingency. In Mexico, un-der the perspective of social transfer of knowledge, far from being a disruptive phenomenon, the evolution that this transfer has followed seems to find –from the confinement and impact of the COVID 19 pandemic– real possibilities of increasing interest for science topics and the opportunity of accessing them through the use of information technologies (ICTs). This is the case of actions for the social transfer of knowledge in a public research center, Centro de Investigaciones Biológicas del Noroeste, S.C. (CIBNOR), in which digital platforms have been consolidated to positively face the times. In this work, detailed, concrete and specific recom-mendations are provided so that the public institutions of research and Higher Education in Mexico can adapt to the new reality imposed by the pandemic as efficiently and functionally as possible in terms of scientific, humanistic and technological research, the training of human resources, and in the linkage and social appropriation of knowledge.